Therapeutic mammaplasty is a safe and effective alternative to mastectomy with or without immediate breast reconstruction. Issue 7 (19th February 2020) - Potter, S; Trickey, A; Rattay, T; O'Connell, R L; Dave, R; Baker, E; Whisker, L; Skillman, J; Gardiner, M D; Macmillan, R D; Holcombe, C; Potter, S; et al.
Abstract: Background: Therapeutic mammaplasty (TM) may be an alternative to mastectomy, but few well designed studies have evaluated the success of this approach or compared the short-term outcomes of TM with mastectomy with or without immediate breast reconstruction (IBR). Data from the national iBRA-2 and TeaM studies were combined to compare the safety and short-term outcomes of TM and mastectomy with or without IBR. Methods: The subgroup of patients in the TeaM study who underwent TM to avoid mastectomy were identified, and data on demographics, complications, oncology and adjuvant treatment were compared with those of patients undergoing mastectomy with or without IBR in the iBRA-2 study. The primary outcome was the percentage of successful breast-conserving procedures in the TM group. Secondary outcomes included postoperative complications and time to adjuvant therapy. Results: A total of 2916 patients (TM 376; mastectomy 1532; mastectomy and IBR 1008) were included in the analysis. Patients undergoing TM were more likely to be obese and to have undergone bilateral surgery than those having IBR. However, patients undergoing mastectomy with or without IBR were more likely to experience complications than the TM group (TM: 79, 21·0 per cent; mastectomy: 570, 37·2 per cent; mastectomy and IBR: 359, 35·6 per cent; P < 0·001). Breast conservation was possible in 87·0 per cent of patients who had TM, and TM did not delay adjuvant treatment. Conclusion: TM may allow high-risk patients who would not be candidates for IBR to avoid mastectomy safely. Further work is needed to explore the comparative patient-reported and cosmetic outcomes of the different approaches, and to establish long-term oncological safety. Graphical Abstract: Therapeutic mammaplasty (TM) may be an alternative to mastectomy, but few well designed studies have evaluated the success of this approach or compared the short-term outcomes of TM with those of mastectomy with or without immediate breast reconstruction (IBR). In this pooled analysis of 2916 patients from the TeaM and iBRA-2 studies, TM was associated with significantly fewer complications than mastectomy with or without IBR, and allowed almost 90 per cent of women to avoid mastectomy. TM may be a safe and effective alternative to mastectomy, especially in high-risk women who may not be offered IBR, but further work including patient-reported outcomes and cost-effectiveness is required before definitive recommendations for best practice can be made. Increasing breast conservation